Achievement of competencies of the students of BRAC non-formal primary schools, 2000-2002 - Nath, Samir Ranjan (BRAC Research and Evaluation Division (RED), 2019)
Using the test instrument developed for Education Watch 2000, this study assessed the achievement of competencies of the students of BRAC non-formal primary schools. Three batches of students (second, third and fourth) completing full cycle of primary education within a time span of four years were the subjects of this study. The findings reveal that with regard to competency achievement the students of all the three batches performed equally. Both inter and intra school variations in performance reduced over time. However, gender gap, where girls were behind the boys, increased sharply. In order to increase overall performance and to reduce gender gap classroom teachings m Mathematics, Social Studies and General Science need to be examined carefully.